2003
DOI: 10.1038/nm821
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the frequency of mouse and human cytotoxic T cells by the Lysispot assay: independent regulation of cytokine secretion and short-term killing

Abstract: Antigen-specific T cells demonstrate several potent effector functions during immune responses. Direct killing of infected cells is crucial for clearing viruses and other intracellular pathogens, but it has been difficult to measure the frequency of cytolytic cells. We have now developed a single-cell assay to measure the number of cytotoxic cells in a population, using a herpes simplex virus amplicon vector to express Escherichia coli beta-galactosidase in mouse or human target cells, and an Elispot to detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
58
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 19 publications
5
58
1
Order By: Relevance
“…Thus, both populations expand significantly and thereby reach a frequency allowing a more effective interaction either directly or through Ag-presenting cell intermediates. It appears that at this stage, the suppression of cytolytic activity is more effective than the suppression of cytokine production or proliferation, i.e., cytotoxicity appears most sensitive to suppression, a notion consistent with observations by others that these effector functions can be regulated independently (27,(34)(35)(36)(37), perhaps because they require different intensity of TCR signaling (38). Also, the cytokine requirement for proliferation of primary and memory CD8 cells may differ, and, hence, Treg may be more efficient in suppressing the proliferation of memory than of primary CD8 T cells.…”
Section: Discussionsupporting
confidence: 86%
“…Thus, both populations expand significantly and thereby reach a frequency allowing a more effective interaction either directly or through Ag-presenting cell intermediates. It appears that at this stage, the suppression of cytolytic activity is more effective than the suppression of cytokine production or proliferation, i.e., cytotoxicity appears most sensitive to suppression, a notion consistent with observations by others that these effector functions can be regulated independently (27,(34)(35)(36)(37), perhaps because they require different intensity of TCR signaling (38). Also, the cytokine requirement for proliferation of primary and memory CD8 cells may differ, and, hence, Treg may be more efficient in suppressing the proliferation of memory than of primary CD8 T cells.…”
Section: Discussionsupporting
confidence: 86%
“…Effector CD8 T cells (45) and cloned CTL lines (10) have cytolytic activity but are unable to produce IL-2 upon restimulation. Snyder et al have reported the generation of CD8 effector cells capable of secreting IFN-␥, but defective for cytolytic activity (46); however, their individual cell-based assay was not designed to detect effectors of the opposite phenotype. Two groups have independently described CD8 T cell populations capable of cytolytic function, but not IFN-␥ secretion (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings in this study further support a model in which calcium signals can play a possible quantitative role in this functional separation (for example, by setting different thresholds for cytotoxic and cytokine programs). We further hypothesize that the relationships between calcium signals and effector functions observed in NK cells could be extrapolatable to T cells and may help explain the dichotomy observed between cytotoxic activity and cytokine production reported for CD8 T cells in several studies (9,(44)(45)(46) (47), kinase activities (48), or transcriptional factors (49) using fusion proteins or reporter mouse (50)] should also allow better resolving the contributions of the dynamics and magnitudes of a wide variety of molecules to functional diversification at the single-cell level. Establishment of this new tool now opens the door to pursue these and many other previously intractable hypotheses on immune cell communication, activation, and function at the single-cell level.…”
Section: Discussionmentioning
confidence: 74%